2020
DOI: 10.1007/s00125-019-05081-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum and urinary biomarker panels with albumin/creatinine ratio in the prediction of renal function decline in type 1 diabetes

Abstract: Aims/hypothesis We examined whether candidate biomarkers in serum or urine can improve the prediction of renal disease progression in type 1 diabetes beyond prior eGFR, comparing their performance with urinary albumin/creatinine ratio (ACR). Methods From the population-representative Scottish Diabetes Research Network Type 1 Bioresource (SDRNT1BIO) we sampled 50% and 25% of those with starting eGFR below and above 75 ml min −1 [1.73 m] −2 , respectively (N = 1629), and with median 5.1 years of follow-up. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…The patients in different CKD groups differed from each other with the incidence of hypertension and diabetes, which is logical, since they are diseases that cause kidney dysfunction. Since diabetes results in significant metabolic alterations reflected in urine other than just presence of glucose and proteins alone 42,43 , we performed additional analyses to exclude the possibility that the classification of CKD is rather due to diabetes-related factors and confirmed that the results are not related with diabetes.…”
Section: Discussionmentioning
confidence: 83%
“…The patients in different CKD groups differed from each other with the incidence of hypertension and diabetes, which is logical, since they are diseases that cause kidney dysfunction. Since diabetes results in significant metabolic alterations reflected in urine other than just presence of glucose and proteins alone 42,43 , we performed additional analyses to exclude the possibility that the classification of CKD is rather due to diabetes-related factors and confirmed that the results are not related with diabetes.…”
Section: Discussionmentioning
confidence: 83%
“…4A, B ). Serum creatinine and urinary albumin to creatinine ratio are routine indicators of kidney pathological changes in type 1 and type 2 diabetes 18 , 19 . As exhibited in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The research presented here is some of the first showings that inclusion of novel and emerging biomarkers of progressive CKD, in addition to kidney function measurements and clinical information traditionally found in patient health records, improves prediction accuracy. Studies using the Scottish Diabetes Research Type 1 Bioresource and the Finish Diabetic Nephropathy cohorts showed that biomarker panels that included KIM-1 and CD27 greatly improved accuracy [ 15 , 17 ]. Moreover, a novel urinary biomarker panel, termed CKD273, and its sub-panels, were more accurate at predicting progressive CKD in the lower grade eGFR categories [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%